Vascularised and modified lower-leg rotationplasty for the treatment of severe infection and bone loss of the proximal femur: a case report - Fischer, Sebastian; Hirche, Christoph; Heppert, Volkmar; Grützner, Paul Alfred; Kneser, Ulrich; Kremer, Thomas (HIP international, 2017)
Case descriptionWe report a reconstructive case in a paraplegic patient, who suffers from a severe proximal femur infection. Aiming at the preservation of the capacity to remain in a seated position to operate a wheelchair, lower leg rotationplasty was considered suitable for reconstruction. Due to severe infection and subclinical femoral artery stenosis, rotationplasty was supercharged by the inferior epigastric artery. Furthermore, extensor tendons of the foot were attached to the acetabulum to facilitate stability of the neo-hip joint.ResultsFollow-up examination 1 year after surgery revealed no complications and a satisfied patient.ConclusionsEspecially in paraplegic patients, lower leg rotationplasty is a possible treatment option for severe femoral infection. Supercharging provides well-vascularised tissue to the former infection site and improves wound healing.
Gesehen am 15.08.2019